Pengembangan Media Pembelajaran Mobile Learning Terhadap Minat Belajar Matematika Siswa SMP Negeri 18 Medan - Meri Lidya Olga Nauli Hutabarat, (Journal of Student Research, 2024)
This study was aimed to develop mobile learning media for students' learning interests at SMP Negeri 18 Medan which meet valid, practical and effective criteria. The research method used is the ADDIE development model which has 5 stages, namely: analysis, design, development, implementation and evaluation. The subjects of this study were 35 students of class IX-2 at SMP Negeri 18 Medan. The results showed that: (1) the development of mobile learning media for students' interest in learning mathematics met very valid criteria with an average percentage of 86.91% based on validation by media experts and an average percentage for material of 83.25% based on validation by material experts; (2) the development of mobile learning media for students' interest in learning mathematics meets practical criteria with an average percentage of 80.47% based on student response questionnaires to learning media; (3) the development of mobile learning media for students' interest in learning mathematics meets the criteria of being effective with an average percentage of 74.68% based on a questionnaire on students' interest in learning mathematics. Based on the results obtained, it can be concluded that the developed mobile learning media for students' interest in learning mathematics is feasible to use.